2013
DOI: 10.1017/s0952523813000230
|View full text |Cite
|
Sign up to set email alerts
|

Distinct synaptic mechanisms create parallel S-ON and S-OFF color opponent pathways in the primate retina

Abstract: Anatomical and physiological approaches are beginning to reveal the synaptic origins of parallel ON- and OFF-pathway retinal circuits for the transmission of short (S-) wavelength sensitive cone signals in the primate retina. Anatomical data suggest that synaptic output from S-cones is largely segregated; central elements of synaptic triads arise almost exclusively from the “blue-cone” bipolar cell, a presumed ON bipolar, whereas triad-associated contacts derive primarily from the “flat” midget bipolar cell, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 96 publications
3
65
0
Order By: Relevance
“…Giant ipRGCs receive inhibitory input from S cones (12), but it is not immediately clear which synaptic inputs mediate this S-off sensitivity (20). Because there is presently no evidence for an S-off bipolar cell in the primate retina (20), the opponent pupil response we observe to S-cone stimulation seems likely explained by the negative S-cone input to ipRGCs.…”
Section: Discussionmentioning
confidence: 85%
“…Giant ipRGCs receive inhibitory input from S cones (12), but it is not immediately clear which synaptic inputs mediate this S-off sensitivity (20). Because there is presently no evidence for an S-off bipolar cell in the primate retina (20), the opponent pupil response we observe to S-cone stimulation seems likely explained by the negative S-cone input to ipRGCs.…”
Section: Discussionmentioning
confidence: 85%
“…31 There is still debate in the literature about the existence of Scone OFF bipolar cells, but if they exist they are very sparse. 32,33 Accordingly, as suggested before, 34 the waveform of the OFF-response in ESCS patients and in our NRL-mutant patients (Fig. 6) reflects mainly the recovery of the S-cones from the light stimulus in the absence of S-cone OFF-center bipolar cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some bipolar cells, depending on the location in the retina, may only contact a specific subset of cone photoreceptors, and as mentioned earlier, can form a ‘private line’. In macaque retina, signals from L and M cones are integrated by the dendrites of ‘diffuse’ and ‘midget’ bipolar cells (Boycott and Wässle, 1999), whereas ‘S cone’ bipolar cells contact exclusively S cone photoreceptors (Dacey, 2000; Dacey et al, 2014; Kouyama and Marshak, 1992; Miyagishima et al, 2014). An S cone selective bipolar cell has also been observed in mouse retina (Haverkamp et al, 2005) and patch-clamp recordings have demonstrated blue ‘ON’ responses from this bipolar cell subtype (Breuninger et al, 2011).…”
Section: Synapse Structure and Connectivity Of Retinal Neuronsmentioning
confidence: 99%